The influence of structure of carbonic acids on the process of its anodic oxidation - Ледовських, В.М.; Ільчак, О.Б. (Proceedings of National Aviation University (archive), 2010)
The article deals with a development of electrochemical method of regeneration of oils in order of its application for the regeneration of products, which forms at storage, transporting and usage of cooling-lubricant oils.The authors of this work have considered the process of anodic oxidation of carbonic acids and made an effort to ground the sequence of its proceeding. In particular, using the polarization curves obtained, it was shown, that process of electrochemical anodic oxidation is controlled by the stage of diffusion of initial materials to the electrode. Also the diffusive mechanism is confirmed by direct dependence of maximum diffusive current of electro-oxidation of carbonic acids as a function of concentration of solutions. The authors of the article explored dependence of the maximum current as a function of molecular mass of acid and have shown, that with the growth of molecular mass the maximum current decreases, the phenomena is explained by reduction in the same sequence the diffusion coefficient.The process of electrochemical regeneration of hydrocarbon mediums at oxidation is determined by the transition of organic acids backwards into hydrocarbons and takes place quickly with a high degree of transformation - 60-70%.Conclusions done by O.B. Ilchak and professor V.M. Ledovskih give rise to possibility to offer some recommendations concerning regeneration of cooling lubricant oils and enrich scientific information in the field of processes of electrochemical oxidation of carboxylic compounds and quantitative control over the given process. Experimental results presented in the articles such as the graphs testify in favor of efficiency of the method of physical- chemical analysis for the achievement of the given task.